Worldviews : an introduction to the history and philosophy of science - DeWitt, Richard. (Wiley-Blackwell, 2010)
"Updated throughout and with three entirely new chapters, Worldviews: An Introduction to the History and Philosophy of Science, Second Edition furthers its reputation as the definitive introductory text on the historical developments and philosophical issues that inform our scientific view of the world around us. Represents an innovative introduction to the history and philosophy of science, designed especially for those coming to the subject for the first time. Updated new edition features the addition of chapters focusing on scientific laws, evolutionary theory, and implications of evolution. Covers the key historical developments and philosophical themes that have impacted our scientific view of the world around us. Analyzes the transitions from the Aristotelian worldview to the Newtonian worldview to a new and currently developing worldview. Explores challenges to the Western scientific worldview brought on by recent discoveries"--